The Entrance of Black Employees into Traditionally White Jobs - Kraut, Allen I. (Academy of Management Journal, 1975)
This article discusses the impact made by the entrance of black employees into traditionally white jobs. The struggle of equal job opportunities for blacks in the U.S. has receded from public attention. There is now more concern about equal employment opportunities for women and promotions for blacks. The study was undertaken at a large manufacturing company to examine the attitudes of people affected by blacks moving into new jobs and gauge its organizational impact. The study was also part of a larger project researching the experiences of new employees. There were implications in the company at that time that black employees did not perform as well as white employees, and that affirmative action programs encouraged the hiring of employees who would otherwise be overlooked.